A Sustaining Operational Performance during Command Training: The Interplay of HR Policy, Leadership Sense-making, and Unit Resilience in a Police Context: The Interplay of HR Policy, Leadership Sense-making, and Unit Resilience in a Police Context - Wibowo, Hendro; Rini Rahmawati; Meiske Claudia (CITACONOMIA, 2026)
Career-level training like SESPIM is critical for leadership development in police forces but creates a unique